DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP PESERTA BPJS KESEHATAN DI RS MELANIA BOGOR - Soedargo, Bayu Prasetyo (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Health is very important for every individual. This will make people more concerned with their health and will make various efforts to maintain their health. On the other hand, the state is obliged to guarantee the health of its citizens. Therefore, the state established a National Health Insurance (JKN) program to provide health insurance for all Indonesian people. This government program is organized by the Health Insurance Administration Agency (BPJS). This study aims to determine the extent of satisfaction of inpatients in Melania Hospital to the services provided by the BPJS Health program. This type of research uses descriptive qualitative methods in finding answers to the level of satisfaction of inpatients in Melania Hospital using the BPJS Health program. This explanation is supported by questionnaire data obtained from 317 inpatients using the BPJS Health program. The results of this study indicate that the quality of services provided by Melania Hospital to BPJS inpatients is good with a total average value of 4.10. For tangible dimensions the average value is 4.10, the reliability dimension the average value is 4.04, the responsiveness dimension the average value is 4.12, the assurance dimension the average value is 4.09 and the empathy dimension the average value is 4.13. The advice given is that Melania Hospital should fix a number of indicators that are still below the standard set by Melania Hospital. Keyword : BPJS Health program, Inpatients, Inpatients satisfaction